PERLINDUNGAN TERHADAP HAK ANAK UNTUK MENIKMATI MASA KECIL DALAM KELUARGA MUSLIM - M. Fadly Daeng Yusuf; Akbarizan (Jotika English and Education Center, 2024)
Protection of Children's Rights from an Islamic sociological perspective, enjoying their childhood in a Muslim family. That child protection is a mandate for parents and conversely, abandoning children is considered an unjust act, both in terms of Islamic law and Law no. 23 of 2002 concerning Child Protection. This paper describes how parents in Muslim families provide educational rights and religious guidance to children in their family. The sociological approach is used as an approach in understanding religion, the importance of the sociological approach in understanding religion is because there are many religious teachings related to social problems, one of the main ones being how to protect children in their childhood, that the majority of Muslim families carry out the protection of educational rights and religious guidance well, while there are 30% is not good and the remaining 20% is not good. There is no reason why children should be blamed, even though children are said to be naughty, as parents and adults see what the child's environment is, children actually need parental guidance. This problem has been taught in Islam because Rasulullah Saw brought Islam as rahmatan lil alamin as was conveyed and practiced by Rasulullah Saw who was patient and loved small children.